Blended Supervision System In Madrasah In Era 4.0 - Ahmad Nasihi; Basuki Wibawa; Popi Puadah (CV ODIS, 2022)
This research is motivated by the contextual phenomenon that virtual learning is not only a way to ensure the continuity of learning during the Covid-19 pandemic but also accelerates the adaptation of Indonesian education to global demands in Era 4.0 where the Internet of Things is the main feature and key in the development of a multidimensional life, including in education. Online distance learning has become a new educational paradigm in Indonesia. However, new problems have also emerged, especially in terms of the supervision of Madrasah/schools. So far, the process of implementing madrasa supervision by supervisors is still mostly done conventionally with manual devices, while the learning process and madrasa activities take place digitally so that supervisory tasks such as monitoring, coaching, mentoring and training professional teachers and their assessment are less effective. Therefore, it is necessary to develop a digital-based madrasa supervision model to facilitate the process of monitoring the implementation of digital-based madrasa education. However, if the supervision is only carried out online, it will not be sufficient because specifically in the process of professional coaching and training, face-to-face meetings are needed between the supervisor and the teacher, and the head of the madrasah. Therefore, a mix of online and offline supervision is needed or a combination of both, is then called blended supervision. Because the scope of blended supervision is very broad and consists of various elements, it is called a supervision system. This refers to the opinion of Abdul Kadir (2014:61) that